(untitled) (Proceedings of the Global Public Health Conference, 2021)
In most mental illnesses, abuse is considered an etiological factor, as a significantly high number of patients report memories of being abused. Yet, there is also a strong evidence base which suggests that recovered memories can be highly unreliable and that they can be creations of the current cognitive biases of individuals. Borderline personality disorder and dissociative disorders have long been linked to a history of abuse. In the current paper, the author discusses three patients; two diagnosed with Borderline personality disorder and the other diagnosed with a dissociative identity disorder. These patients were treated by the author in the private sector and analysis of the weekly treatment records were used for the findings of the current paper. All these patients were females who started treatment in their teenage years. All exhibited a treatment-resistant clinical picture and experienced many short-spaced relapses. After the lapse of about six months into psychotherapy, they accidentally discovered a strong memory of an abuse incident, which could not be traced to any known circumstances of their lives. The memory was highly unlikely to have occurred in reality. Yet, the discovery of the memory and subsequent cognitive processing of the implications and the visual content of these memories marked a notable improvement in the patient. With further treatment, all three were in the remission stage. Therefore, the author feels that patients may have abusive memories, which may or may not be necessarily linked to real life circumstances, yet may strongly influence the patient’s symptoms. However, despite the validity of these memories, it is clear that these memories should be treated as significant by clinicians who treat mental illnesses.